2021
DOI: 10.15218/zjms.2021.032
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-androgenic steroid use among bodybuilders in Erbil city

Abstract: Background and objective: Anabolic-androgenic steroids are synthetic testosterone derivatives with a longer duration of action than physiological androgens. They are abused by bodybuilders because of their potential to enhance muscle strength. Serious medical and psychological complications may be associated with their non-medical use. This study aimed to determine the prevalence of anabolic androgenic steroids among bodybuilders and their awareness of health-related risks. Methods: A cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…However, studies have found that athletes obtained these drugs from many illegal sources including their coaches (Aldarweesh and Alhajjaj, 2020) and friends (Althobiti et al, 2018). Incidentally, poor knowledge of the negative effects of AAS and negative attitude towards AAS use, have been reported across studies in Nigeria (Afolayan, 2012;Ijadunola et al, 2018) and outside Nigeria (Althobiti et al, 2018;Ahmed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have found that athletes obtained these drugs from many illegal sources including their coaches (Aldarweesh and Alhajjaj, 2020) and friends (Althobiti et al, 2018). Incidentally, poor knowledge of the negative effects of AAS and negative attitude towards AAS use, have been reported across studies in Nigeria (Afolayan, 2012;Ijadunola et al, 2018) and outside Nigeria (Althobiti et al, 2018;Ahmed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%